Gelatin nanoparticle-mediated intranasal delivery of substance P protects against 6-hydroxydopamine-induced apoptosis: an in vitro and in vivo study - Lu CT; Jin RR; Jiang YN; Lin Q; Yu WZ; Mao KL; Tian FR; Zhao YP; Zhao YZ (Dove Medical Press, 2015)
Cui-Tao Lu,1,2 Rong-Rong Jin,2 Yi-Na Jiang,2 Qian Lin,2 Wen-Zhe Yu,2 Kai-Li Mao,2 Fu-Rong Tian,2 Ya-Ping Zhao,1,* Ying-Zheng Zhao2,* 1The Second Affiliated Hospital, Wenzhou Medical University, 2School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, People’s Republic of China *These authors contributed equally to this work Background: The aim of this study was to investigate the protective role of intranasally administered substance P-loaded gelatin nanoparticles (SP-GNPs) against 6-hydroxydopamine (6-OHDA)-induced apoptosis in vitro and in vivo, and to provide a new strategy for treating brain pathology, such as Parkinson’s disease.Methods: SP-GNPs were prepared by a water-in-water emulsion method, and their stability, encapsulating efficiency, and loading capacity were evaluated. PC-12 cells were used to examine the enhancement of growth and inhibition of apoptosis by SP-GNPs in vitro using MTT assays. In the in vivo study, hemiparkinsonian rats were created by intracerebroventricular injection of 6-OHDA. The rats then received intranasal SP-GNPs daily for 2 weeks. Functional improvement was assessed by quantifying rotational behavior, and the degree of apoptosis was assessed by immunohistochemical staining for caspase-3 in the substantia nigra region.Results: PC-12 cells with 6-OHDA-induced disease treated with SP-GNPs showed higher cell viability than their untreated counterparts, and cell viability increased as the concentration of substance P (SP) increased, indicating that SP could enhance cell growth and inhibit the cell apoptosis induced by 6-OHDA. Rats with 6-OHDA-induced hemiparkinsonism treated with SP-GNPs made fewer rotations and showed less staining for caspase-3 than their counterparts not treated with SP, indicating that SP protects rats with 6-OHDA-induced hemiparkinsonism from apoptosis and therefore demonstrates their functional improvement.Conclusion: Intranasal delivery of SP-GNPs protects against 6-OHDA-induced apoptosis both in vitro and in vivo.Keywords: gelatin nanoparticles, intranasal delivery, substance P, 6-hydroxydopamine, apoptosis, Parkinson’s disease